2012
DOI: 10.5812/asjsm.34536
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hypertrophic Burn Scar: A Comparison between the Efficacy of Exercise-Physiotherapy and Pressure Garment-Silicone on Hypertrophic Scar

Abstract: Purpose: Our study aims to investigate the effectiveness of other treatment methods for burn related scarring and to determine the possibility of their routine administration in similar clinical settings.Methods: Through a prospective study, 66 patients were enrolled to receive either the conventional pressure garment therapy (PGT) and Silicone (control group) or exercise and physiotherapy (case group). Patients were visited regularly to be examined for the status of their scars' regression, limbs' dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…31,43,44 The survey was designed to establish current practice concerning the length of time PGT is used and the rationale behind the recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…31,43,44 The survey was designed to establish current practice concerning the length of time PGT is used and the rationale behind the recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of active physical therapy over passive modalities as it relates to painful scar are supported by the literature. 48 As is the case in many painful conditions where emphasis is placed on mobilization and increasing range of motion, strength and flexibility, limitations due to pain are a significant challenge for many patients. Strategies to reduce pain are critically important to reduce the barriers from progressing with exercise techniques and multidisciplinary techniques should be established.…”
Section: Conservative Treatment Approachesmentioning
confidence: 99%
“…MSCs remain at the site of the skin wound, even after the wound has been closed. These cells play a pivotal role in almost all of the processes of inflammation, fibrosis, tissue repair, angiogenesis, wound contraction, scar development, and granulation tissue formation [117][118][119][120]. The studies have shown that mesenchymal stem cells have immunomodulatory effects such as inhibition of proliferation and reduced function in various immune cells, including natural killer (NK) cells, dendritic cells (DC), and lymphocytes [121][122][123].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%